Bacterial cellulose‐hydroxyapatite composites with osteogenic growth peptide (OGP) or pentapeptide OGP on bone regeneration in critical‐size calvarial defect model. Issue 10 (7th July 2015) - Pigossi, Suzane C.; de Oliveira, Guilherme J. P. L.; Finoti, Livia S.; Nepomuceno, Rafael; Spolidorio, Luis Carlos; Rossa, C.; Ribeiro, Sidney J. L.; Saska, Sybele; Scarel‐Caminaga, Raquel M.
Abstract This study aimed to evaluate the potential of bacterial cellulose‐hydroxyapatite (BC‐HA) composites associated with osteogenic growth peptide (OGP) or pentapeptide OGP(10–14) in bone regeneration in critical‐size calvarial defects in mice. In this study, the BC‐HA, BC‐HA‐OGP, and BC‐HA‐OGP(10–14) membranes were analyzed at 3, 7, 15, 30, 60, and 90 days. In each period, the specimens were evaluated by micro‐computed tomography (µCT), descriptive histology, gene expression of bone biomarkers by qPCR and VEGFR‐2 (vascular endothelial growth factor) quantification by ELISA. Three days post‐operative, Runx2, Tnfrsf11b and Bglap bone biomarkers were upregulated mainly by BC‐HA OGP and BC‐HA OGP(10–14) membranes, suggesting an acceleration of the osteoblast differentiation/activity with the use of these biomaterials. At 60 and 90 days, a high percentage of bone formation was observed by µCT for BC‐HA and BC‐HA OGP(10–14) membranes. High expression of some bone biomarkers, such as Alpl, Spp1, and Tnfrsf11b, was also observed for the same membranes on days 60 and 90. In conclusion, the BC‐HA membrane promoted a better bone formation in critical‐size mice calvarial defects. Nevertheless, incorporation of the peptides at the concentration of 10−9 mol L−1 did not improve bone regeneration potential in the long‐term. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3397–3406, 2015.